A physiologically based pharmacokinetic model of ketoconazole and its metabolites as drug-drug interaction perpetrators - Marok, Fatima; Wojtyniak, Jan-Georg; Fuhr, Laura Maria; Selzer, Dominik; Schwab, Matthias; Weiß, Johanna; Haefeli, Walter E.; Lehr, Thorsten (Pharmaceutics, 2023)
The antifungal ketoconazole, which is mainly used for dermal infections and treatment of Cushing’s syndrome, is prone to drug-food interactions (DFIs) and is well known for its strong drug-drug interaction (DDI) potential. Some of ketoconazole’s potent inhibitory activity can be attributed to its metabolites that predominantly accumulate in the liver. This work aimed to develop a whole-body physiologically based pharmacokinetic (PBPK) model of ketoconazole and its metabolites for fasted and fed states and to investigate the impact of ketoconazole’s metabolites on its DDI potential. ...
Gesehen am 05.12.2023